Know your adjuncts - Jiti Bhuvandas Palliyani; Suyog Dharmadhikari; Devanand Shetty; Arvind Shetty; Pooja Wadkar (Wolters Kluwer Medknow Publications, 2023)
Introduction: Knowledge of oral health is a prerequisite for psychological and physical health. The two most prevalent oral diseases, dental caries and periodontal diseases, are largely preventable through professional and self-care activities. With a boom in over-the-counter self-care products available for better oral health, it is imperative to know the awareness with regard to them, among the general population. The objective of this study was to survey the awareness regarding the use of interdental aids and chemical plaque control among the general population. Materials and Methods: A questionnaire comprising 17 close-ended questions was handed down to the 473 patients at the outpatient department of DY Patil School of Dentistry, Navi Mumbai, to gather information regarding their awareness and technique of using interdental aids and chemical plaque control. The collected data were statistically analyzed using the SAS software. Results: According to the analysis done using the SAS software, 58% lacked awareness of inter dental aids whereas 14% were not aware of mouth rinses. At the same time, 98% had no knowledge about water irrigation devices or the side effects of mouth rinses. Conclusion: The study indicated that as compared to oral rinses, the awareness among the masses regarding the use of interdental aids and their helpfulness in prevention of dental caries and periodontal diseases is lacking. There is a need for a dentist to take the front seat in patient education in terms of mechanical and chemical plaque control adjuncts.